PENINGKATAN HASIL BELAJAR DAN DISIPLIN SISWA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING - Ginting, Pelta; Yosefa, Santa (Universitas Negeri Medan, 2024)
This research aims to implement the Contextual Teaching and Learning model to improve both student learning outcomes and discipline at St. Petrus Medan Elementary School. The classroom action research (PTK) involved 28 students from Phase C Class V of the 2023/2024 academic year. The research method steps start from Associating, Cooperation, Experiencing, Applying, Transferring. Data collection methods include tests, observation, and documentation. Qualitative descriptive analysis is used with process and product success criteria. Results showed significant increases in applicability such as Associating (67% to 83%), Cooperation (58 to 67%), Experiencing (83% to 100%), Applying (67% to 83%), Transferring (83% to 100%). Likewise, there was an increase in student discipline such as doing assignments on time (5.8% to 14.2%), paying attention to teacher explanations well (5.3% to 15.6%), maintaining order in class (3.7% to 12.9%), Involvement in classroom discussions (6.8% to 14.5%), Arriving to school on time (8% to 15.1%). Student learning outcomes also improved, such as Advanced Category (from 46% to 68%), Cakap (from 18% to 25%). Viable (from 29% to 0%), Growing (from 7% to 7%).